Against the Grain and Over the Line: Reflections on Comparative Methodology - David M. Freidenreich (Religions, 2018)
This article distills theoretical arguments that I advance in Foreigners and Their Food, arguments relevant to a wide range of religious studies scholars. In addition, it makes the case for comparison as a method that sheds light not only on specific comparands and the class of data to which they belong but also on the very boundaries which the comparison transgresses. Through a comparison of Latin Christian and Shiʿi Islamic discourse about the impurity of religious foreigners, I illustrate methods by which religious authorities develop and transmit conceptions of foreigners. I then analyze this case study using Oliver Freiberger’s “Elements of a Comparative Methodology” while assessing the strengths and limitations of Freiberger’s methodical framework. I offer personal reflections on the process of conducting comparative scholarship, advice for those embarking on this demanding yet rewarding approach to the study of religion, and desiderata for further reflection on comparative methodology.